KEPUASAN KONSUMEN PADA RESTORAN ADEM RESTO KOTA BENGKULU - Putril Hidayati Upik; Ratnawili Ratnawili (UM. Bengkulu, 2022)
This study aimed to determine the effect of service quality, facilities,Â prices toward customersâ€™ satisfaction of Adem Resto Restaurant in Bengkulu City. This study used qualitative research method. The total sample of this research was 90 customers of Adem Resto Restauran in Bengkulu City that taken by using accindental sampling technique. The data was collected by using observation and questionnaire. The data was analyzed by using multiple regression analysis and coefficients of determination. The results of the research show that the regression equation analysis is Y= 0.761 + 0.335 (X1) + 1.237 (X2) + 0.683 (X3) The value (constant) of 0.761 means that if the variables of Service Quality (X1), Facilities (X2) and Price (X3), equal to zero, the variable satisfaction of the congregation (Y) will remain at 0.761. The regression coefficient of Service Quality (X1) of 0.335. It states that every one unit increase in the value of the Service Quality variable can increase the value of the variable satisfaction of pilgrims (Y) by 0.335 assuming that the Facility (X2) and Price (X3) variables are considered constant or = 0. The Facility regression coefficient (X2) of 1,237 states that every one unit increase in the value of the Facility variable can increase the value of the pilgrim satisfaction variable (Y) by 1.237, assuming that the variables of Service Quality (X1) and Price (X3) are considered constant or = 0. Price regression coefficient (X3) of -0.683 states that every one unit decrease in the value of the Price variable can increase the value of the variable satisfaction of pilgrims (Y) by 0.683, assuming that the variables of Service Quality (X1) and Facilities (X2) are considered constant or = 0.